2019
DOI: 10.1109/tsp.2018.2877205
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Vector Perturbation Precoding: The Blessing of Approximate Message Passing

Abstract: Vector perturbation (VP) precoding is a promising technique for multiuser communication systems operating in the downlink. In this work, we introduce a hybrid framework to improve the performance of lattice reduction (LR) aided precoding in VP. First, we perform a simple precoding using zero forcing (ZF) or successive interference cancellation (SIC) based on a reduced lattice basis. Since the signal space after LR-ZF or LR-SIC precoding can be shown to be bounded to a small range, then along with sufficient or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 43 publications
(113 reference statements)
0
19
0
Order By: Relevance
“…The noise spectral density and transmission bandwidth are set to -170 dBm/Hz and 1 MHz, respectively. For comparison, we examine the performance of the conventional LS-BOMP [11], MMSE-BOMP [29], and approximate message passing (AMP) algorithm [30]. When generating nonzero values in the LDS codebook, we use an i.i.i.…”
Section: A Simulation Setupmentioning
confidence: 99%
“…The noise spectral density and transmission bandwidth are set to -170 dBm/Hz and 1 MHz, respectively. For comparison, we examine the performance of the conventional LS-BOMP [11], MMSE-BOMP [29], and approximate message passing (AMP) algorithm [30]. When generating nonzero values in the LDS codebook, we use an i.i.i.…”
Section: A Simulation Setupmentioning
confidence: 99%
“…We shall adopt this notion and observe the influence of LR on the plain ZFP and the ZF-THP approaches, instead of using the potentially ambiguous terminology of lattice reduction aide broadcast precoding [164], the latter of which essentially constitutes extensions to the vector perturbation scheme we will cover later. In essence, approximate lattice precoding heuristically solves the closest vector problem with preprocessing (CVPP), the solution of which can be further used as preprocessing for other schemes, such as the approximate message passing algorithm of [165]. However, the strict-sense CVPP in lattice theory typically exploits the geometry of the Voronoi cell and utilizes exponential-sized memory/buffer for very high dimensional lattices [166], whereas LRMUP algorithms simply acquire a good basis to work with for low to medium dimensional lattices.…”
Section: B Approximate Lattice Precodingmentioning
confidence: 99%
“…In AMP algorithm [23] ZF/SIC is used for initial guess of maximal error distance which is practically very close to small scale sphere decoding and certain probabilities also exist in which large dimensions contain slight error distance. Ternary distribution is used [32] for such scenarios. Empirical study has also proved that maximum portion of errors can be removed by using ternary distribution {−1, 0, 1} for PX (x q ).…”
Section: Algorithm 1 the Amp Algorithmmentioning
confidence: 99%
“…In [31], it is shown that the calculation of the posterior mean function (known as threshold function [28]) of AMP algorithm for small values of noise variance will become numerically unstable. In [32], two threshold functions have been designed to mitigate or overcome the computational complexities of AMP algorithm. The AMP algorithm with threshold function using ternary distribution is known as AMPT whereas, the one with threshold function using Gaussian distribution is known as AMPG [32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation